Efektifitas Pengelolaan Wakaf (Studi Kecamatan Baktiya Barat Kabupaten Aceh Utara) - Hidayatina Hidayatina; Mahdalena Nasrun (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The implementation of regulations regarding the authority of waqf managers in Aceh, namely Baitul Mal, the Office of Religious Affairs (KUA) and the Indonesian Waqf Board (BWI), will certainly affect the effectiveness of waqf management, including West Baktiya District, North Aceh Regency. This research aims to determine the effectiveness of waqf waqf management in Baktiya Barat sub-district, North Aceh sub-district. This type of research is field research using qualitative descriptive methods. The results of the research show that the management of waqf by the KUA of West Baktiya sub-district with the implementation of waqf management by nadzir in every gampong in Baktiya Barat sub-district, the causes are (1) the KUA rarely goes to the gampong - (2) from the nadzir, the KUA still only receives limited reports that there is waqf land in the gampong, while there are no reports from nadzir regarding the management of waqf assets in West Baktiya District and frequent changes of nadzir before the term of office ends (3) problems related to waqf assets, including many waqf lands that do not have waqf pledge deeds and the sale and purchase deed, ┬áwaqf land are revoked by the heirs.